TMS 2017 146th Annual Meeting & Exhibition Supplemental Proceedings - TMS, The Minerals, Metals & Materials Society; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This collection features papers presented at the 146th Annual Meeting & Exhibition of The Minerals, Metals & Materials Society.
Solid State Precipitation -- Hydride Precipitates in Zirconium Alloys: Evolution of Dissolution and Precipitation Temperatures during Thermal Cycling Correlated to Microstructure Features -- Analysis of Beta´ Cu4Ti Precipitation in Cu-Ti Alloys by Conventional and Diffusion-couple Methods -- Carbide Precipitation in a Low-alloy Ferritic Steel -- Part 21: Student-Run Symposium: Building Bridges - Connecting Academic and Industry Research -- Fundamental Principles for a Successful Collaboration between University and Metalworking Industries.
Keywords: Metals; Materials -- Analysis; Materials; Metals and Alloys; Characterization and Analytical Technique; Materials Engineering